2020
DOI: 10.1093/jnci/djaa136
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Associations Between Chemotherapy, Chronic Conditions, and Neurocognitive Impairment in Acute Lymphoblastic Leukemia Survivors: A Report From the Childhood Cancer Survivor Study

Abstract: Background The purpose was to examine associations between treatment and chronic health conditions with neurocognitive impairment survivors of acute lymphoblastic leukemia (ALL) treated with chemotherapy only. Methods This cross-sectional study included 1,207 ALL survivors (54.0% female; mean age 30.6 years) and 2,273 siblings (56.9% female; mean age 47.6 years), who completed the CCSS Neurocognitive Questionnaire. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…Notably, these chronic health conditions were associated with worse outcomes on multiple self-reported behavioral measures, even after accounting for CRT status. This finding is similar to those of emerging studies that identified the contributions of chronic health conditions resulting from childhood cancer therapies to emotional distress and neurocognitive impairment (22,23,25). These observations have important clinical implications.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Notably, these chronic health conditions were associated with worse outcomes on multiple self-reported behavioral measures, even after accounting for CRT status. This finding is similar to those of emerging studies that identified the contributions of chronic health conditions resulting from childhood cancer therapies to emotional distress and neurocognitive impairment (22,23,25). These observations have important clinical implications.…”
Section: Discussionsupporting
confidence: 86%
“…The severity of the conditions was graded according to the National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE version 4.03) (41), which defines the severity of the health conditions as asymptomatic/mild symptoms (grade 1), moderate symptoms requiring minimal interventions (grade 2), severe/disabling symptoms requiring extensive interventions (grade 3), and life-threatening conditions (grade 4). For this study, the health conditions of interest were limited to the cardiopulmonary, endocrine, metabolic, psychiatric, neurological and hearing/vision systems, as these have been associated with neurocognitive function in cancer survivors (15,22,23,25,42). Only chronic health conditions with a reported age of onset during or after the completion of cancer treatment were included.…”
Section: Clinical and Treatment Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study consisted of 20 patients, of which eight (33.3%) were women, between 16 and 50 years old, with an average age of 37.75 ± 11.63 years and 12 men (66.7%) with a mean age of 28.50 ± 18.05 years, this range between 15 and 64 years, coincide with other authors, who indicate that men have a higher incidence, in acute lymphoblastic leukemia [10]. Seven patients presented comorbidities, without statistical association with sex (p = 0.370) (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…Studies investigating the neurocognitive consequences of chemotherapy during childhood (see Figure 1 ) have also found impairments to working memory and executive function [ 20 , 67 , 68 , 69 ], as well as processing speed, task efficiency, attention, memory and learning [ 70 , 71 , 72 ]. An important association has been made between these functions and self-regulatory behaviour, such as effective coping [ 73 ].…”
Section: Cognitive-affective Appraisalmentioning
confidence: 99%